ANALYSIS OF THE CURRENT SITUATION WITH THE PROCESS OF DEINSTITUTIONALISATION IN THE REPUBLIC OF MACEDONIA WITH A FOCUS ON 10 TARGET MUNICIPALITIES (Годишен зборник на Филозофски факултет - Скопје, 2021)
The social protection system of the Republic of Macedonia consists of centers, institutions, measures, activities, and norms realized within the exercise of rights and services’ provision to citizens in the area of social protection. The system is upgraded through the expertise of the institutes for social protection (which carry out development programs and work on the professional specialization of workers depending on the needs of beneficiaries and international standards), situation monitoring and work planning, keeping records as well as the implementation of supervision and research in this area.The process of Deinstitutionalization of people with disabilities will be impossible without a strong network of service providers, the private sector from that region because both of them are relevant stakeholders to develop models of education, employment, social and health services to facilitate independent living of people with disability.Through this approach, tailored models, addressing the needs of the targeted individuals in one institution, as representatives of people with disabilities, have been developed in all ten municipalities and should be included in national policies. More specifically, by adapting protocols, guidelines, training modules to ensure accessibility and acceptability of services for people with disabilities in the above 10 mentioned municipalities, barriers to existing services will be removed and the attainment of the highest possible level of services for people with disabilities will be sought 1.